Lightweight Photovoltaic Composite Structure on Stratospheric Airships - Xinyun Zhang; Kangwen Sun; Dongdong Xu; Shijun Guo (Advances in Materials Science and Engineering)
A semirigid solar array is an efficient energy system on the surface of stratospheric airships for utilizing the solar energy, which we believe that it has succeeded in providing some impressive results for conceptual design. This paper developed a lightweight photovoltaic composite structure (LPCS) according to the characteristics of the stratospheric airship capsule. In order to improve the flexibility of the solar cell, we studied the mechanical properties in the different thicknesses of the honeycomb core for LPCS by FEM software and three-point bending test, and we also launched experiments to measure the temperature difference between upper and lower surfaces of the LPCS test samples under different solar radiation flux conditions. The experimental data were examined to evaluate the mechanical properties and thermal insulation performances of LPCS. Considering the quality of the whole structure, the paper finally comes up with the conclusion of the optimal thickness of the honeycomb core with further detailed descriptions.